2013
DOI: 10.1071/hc13191
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of inhaler technique used by people with asthma or chronic obstructive pulmonary disease

Abstract: INTRODUCTION: Asthma and chronic obstructive pulmonary disease (COPD) are ongoing concerns to the health system. Poor inhaler technique results in less than optimal delivery of medicine to the lungs and consequent inadequate symptom control. AIM: This study aimed to assess inhaler technique amongst people with asthma and/or COPD. The secondary aims were to investigate who provided education on inhaler technique and whether age, gender or ethnicity was associated with poor inhaler technique. METHODS: People wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 24 publications
2
63
1
1
Order By: Relevance
“…[4] Despite the advantages of this mode of drug administration, many studies report suboptimal inhaler technique with all device types including metered-dose inhalers (MDIs), MDI use with spacer devices, and breathe-actuated dry powder inhalers (DPIs). [5][6][7][8] Poor patient self-administered inhaler technique is often related to poor outcomes such as increased emergency room visits, use of short-course steroids, antimicrobial use, and poor disease control. [5] Using an inhaler appropriately requires a certain degree of coordination and dexterity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Despite the advantages of this mode of drug administration, many studies report suboptimal inhaler technique with all device types including metered-dose inhalers (MDIs), MDI use with spacer devices, and breathe-actuated dry powder inhalers (DPIs). [5][6][7][8] Poor patient self-administered inhaler technique is often related to poor outcomes such as increased emergency room visits, use of short-course steroids, antimicrobial use, and poor disease control. [5] Using an inhaler appropriately requires a certain degree of coordination and dexterity.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, several studies have shown that patients often exhibited suboptimal technique in as little as three days after initial training. [6,13] Assessing a patient's ability to correctly use an inhaled medication is frequently based on checklists [7,8,[14][15][16] or essential steps described in manufacturer instructions and national guidelines. However, there is no standardized checklist for technique assessment used across research studies in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Inhalation therapy is of paramount importance in the treatment of respiratory conditions. 3,4,[14][15][16][17][18][19] Regarding IT, evidence in the literature suggests that 50%-100% of patients perform errors while using their inhalers. 3,4,[14][15][16][17][18][19] Regarding IT, evidence in the literature suggests that 50%-100% of patients perform errors while using their inhalers.…”
Section: Introductionmentioning
confidence: 99%
“…As FEV worsens, then long‐acting beta‐agonists and muscarinic antagonists are introduced as combination therapy with the final option being to introduce inhaled corticosteroids [7]. The effectiveness of this approach is determined by the patient's ability to use an inhaler correctly[8] and by their willingness to use it as agreed with the prescriber [9]. Devices such as the In‐Check Dial (Clement Clarke International, Harlow, UK) are available to ensure that the type of inhaler selected for a patient is appropriate for their pulmonary function [10].…”
Section: Introductionmentioning
confidence: 99%